Analisis Dampak Sektor Pariwisata terhadap Kesejahteraan Pedagang di Kota Banjarmasin - Kristo; Yunita Sopiana (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study was conducted to (1) analyze the impact of the tourism sector on thewelfare of traders in the tourist area of the Siring Sungai Martapura Park in the City ofBanjarmasin (2) to analyze the differences in the welfare level of traders who utilize thetourism sector before and after the development of tourism in the tourism area of the SiringRiver Martapura Park Banjarmasin City. In this study, Respondents were 38 people,namely traders who are still active around the Siring Sungai Martapura Park inBanjarmasin City. This research is a qualitative descriptive study. In this study, datacollection methods were interviews in the form of cake, observation, documentation, andliterature study. The results of this study prove the positive impact of the tourism sector onthe welfare of traders around the Banjarmasin tourist attraction used in this study, namelythe Siring Sungai Martapura Park Banjarmasin City viewed from the tourism sector whichgives an impact on increasing income before and after the development of tourism,education level, the level of health, and living conditions that indicate merchants who haveincreased welfare before and after utilizing the tourism sector. The resulting negativeimpact is the dependence on the existing tourism sector because it depends on tourist visits.The tourism sector is used as an indicator in the study. This is a tourist visit while publicwelfare indicators are income, expenditure, health, education, and living conditions.